Performance leadership - Leonard, Karen Moustafa. (Human resource management and organizational behavior collection., 2016)
A daunting aspect of management is the performance appraisal. It has become a byword for unfairness and irritation among employees. Some management writers are even proposing in doing away with it. We agree that the current method of appraisal is unsustainable and counterproductive. In this book, we discuss Performance Leadership--the idea of leading employee performance, which should be the focus of management. Just doing appraisal or evaluation is not enough. Managers must incorporate the entire model of performance management and use it to lead within their workgroup, department, or organization. We walk managers through the steps of Performance Leadership, discussing the benefits and pitfalls of each step. The idea of making performance management work as a leadership style is new and simple, but it takes dedication to complete the task. This book is valuable for supervisors, managers, human resource staff, and others--anyone who needs to manage performance!